2015
DOI: 10.3144/expresspolymlett.2015.20
|View full text |Cite
|
Sign up to set email alerts
|

Ductile-brittle transition behaviour of PLA/o-MMT films during the physical aging process

Abstract: Abstract. The ductile-brittle transition behaviour of organo modified montmorillonite-based Poly(lactic acid) films (PLA/o-MMT) was analysed using the Essential Work of Fracture (EWF) methodology, Small Punch Tests (SPT) and Enthalpy relaxation analysis. While the EWF methodology could only be applied successfully to de-aged samples, small punch test (SPT) was revealed as more effective for a mechanical characterization during the transient behaviour from ductile to brittle. According to differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…For further loading, these voids grew with extensive fibrillation (shear yielding) which gives rise to the distortion and coalescence of the holes with ridge formation. Similar observations have been reported in the literature [48,49].…”
Section: Evaluation Of the Clay Interactions By Pukanszky's B Factorsupporting
confidence: 92%
“…For further loading, these voids grew with extensive fibrillation (shear yielding) which gives rise to the distortion and coalescence of the holes with ridge formation. Similar observations have been reported in the literature [48,49].…”
Section: Evaluation Of the Clay Interactions By Pukanszky's B Factorsupporting
confidence: 92%
“…Tsuji and Sawada also observed the strong enthalpy relaxation and found that physical ageing increased both the glass transition temperature and the enthalpy of the glass transition, but did not increase the crystallinity. Also, the ageing behaviour of plasticised PLLA, PLLA blends and composites have been shown to broadly exhibit the same trends as those observed for pure PLLA.…”
Section: Introductionmentioning
confidence: 54%
“…28,29 The accompanied decrease in the molecular mobility was attributed to a configurational rearrangement of chain segments from a totally disordered configuration for unaged materials to locally ordered ones for aged samples below T g . This phenomenon is commonly called physical ageing process, which is the principal factor responsible for the advanced PLA brittleness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This phenomenon is commonly called physical ageing process, which is the principal factor responsible for the advanced PLA brittleness. 28,29 The accompanied decrease in the molecular mobility was attributed to a configurational rearrangement of chain segments from a totally disordered configuration for unaged materials to locally ordered ones for aged samples below T g . 30 Under the experimental conditions used, results suggest that the addition of silica nanofillers did not seem to hamper these restricted molecular motions, which lead to the ductile-brittle transition.…”
Section: Mechanical Propertiesmentioning
confidence: 99%